(untitled) (Emancipação, 2021)
Social vulnerability is a polysemic theoretical category that points to many possibilities for reflection and measurement in contexts that reveal the conditions in which families that use public social assistance policies live. In the State of Paraná, the government established the Paranaense Family Programme since 2012, as a strategy to promote social protection to families in socially vulnerable situations. The Program proposes planned and intersectoral actions, articulating health, education, housing, farming and work policies and aims to consolidate an integrated protection network for registered families. That said, this article aims to demonstrate the relevance of the Vulnerability Index of Families in Paraná as a strategy for user access to the Paranaense Family Programme and its benefits. It was based on bibliographic and documentary research using mainly information provided by the government of the State of Paraná and the Paranaense Family Programme Monitoring System. The article of descriptive character was organized so as to highlight the category social vulnerability and its relationship with the Família Paranaense Programme and according to the configuration of the Index of Vulnerability of Families of Paraná in aspects that express the concrete conditions in which families participating in the programme live in the municipality of Ponta Grossa/PR. Lastly, It is concluded that the indicators are potential instruments for monitoring and evaluating social policies and can point out strategies of an intersectoral character to face the concrete demands presented by the users of the Social Assistance policy in the local reality.